Union of the Comoros : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2006)
The dominant role of remittances in Comoros's economy presents policymakers with important challenges and opportunities. Fiscal decentralization is a pillar of national reconciliation in Comoros. To make decentralization work better, more revenue and expenditure responsibilities could be devolved to the islands. The paper also presents statistical data on gross domestic product, indicators of tourism, consolidated government financial operations, breakdown of staffing levels, summary statement of banks, balance of payments, payment arrears and service payments, summary of the tax system, and other economic indices.